Peran Desain Learning Trajectory Nilai Tempat Bilangan Berbantukan Video Animasi Terhadap Pemahaman Konsep Nilai Tempat Siswa Kelas II SD - Novita , Rita; Putra , Mulia (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2017)
Understanding the concept of place value is very important for students in mastering the further mathematical concepts. However, the numbers of studies have shown that, students understanding of place value concepts are still problematic, because the place value learning experience in the classroom less meaningful where the learning is directly exposed to master the number of algorithms. In fact, should the place value learning should be emphasized to the students real experience with concrete objects to reinvent important concepts in place value. Therefore, this study aimed to investigate the role place value learning trajectory that have been developed through PMRI approach by using video animation toward student’s understanding of place value concept in second grade primary school. To achieve these aims, this study using design research (Akker model), where the research include three phases preparing for the experiment, Experiment in the classroom, and Retrospective analysis. This discussion focuses only Retrospective analysis to explain the role of learning trajectory developed towards the understanding of the place value concept. The study involved 15 second gare students of SDN 19 in Banda Aceh. Teaching experiment results showed that the learning trajectory that was developed give students the opportunity to reinvent and understand the concept of place value.